2017
DOI: 10.4244/eij-d-17-00078
|View full text |Cite
|
Sign up to set email alerts
|

Reduced periprocedural mortality and bleeding rates of radial approach in ST-segment elevation myocardial infarction. Propensity score analysis of data from the ORPKI Polish National Registry

Abstract: The radial approach was associated with a lower incidence of periprocedural death in STEMI patients as well as a significant reduction of bleeding complications at the access site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…Prospectively collected data on PCI practice in Poland were obtained from the ORPKI Polish National dataset, which is coordinated nationwide by Jagiellonian University Medical College in cooperation with AISN PTK (Association of Cardiovascular Interventions Polish Cardiac Society). Database characteristics and data collection methods have been previously presented [8,9]. Patients were categorized according to whether they had undergone PCI of SVG or the right/left internal mammary artery (IMA).…”
Section: Study Population Design and Definitionsmentioning
confidence: 99%
“…Prospectively collected data on PCI practice in Poland were obtained from the ORPKI Polish National dataset, which is coordinated nationwide by Jagiellonian University Medical College in cooperation with AISN PTK (Association of Cardiovascular Interventions Polish Cardiac Society). Database characteristics and data collection methods have been previously presented [8,9]. Patients were categorized according to whether they had undergone PCI of SVG or the right/left internal mammary artery (IMA).…”
Section: Study Population Design and Definitionsmentioning
confidence: 99%
“…A more detailed description of the registry was presented elsewhere. 14,15 The objective of the present study was to analyze long -term survival of patients with OHCA identified in the ORPKI registry for the Świętokrzyskie Province, estimate their probability of survival, and evaluate risk factors.…”
mentioning
confidence: 99%
“…Data on PCI practice in Poland were obtained from the ORPKI Polish National dataset which is coordinated nationwide by Jagiellonian University Medical College in cooperation with AISN PTK (Association of Cardiovascular Interventions–The Polish Cardiac Society). The method of collecting data in the ORPKI registry was presented in previously published works [ 9 , 10 ]. Consecutive patients with COPD were included.…”
Section: Methodsmentioning
confidence: 99%